Patterns of plant diversity and cultural meaning in a rural landscape in the Albany Thicket: effects of land-use and topography - Ngqiyaza, Nozuko Princess (Rhodes University, Faculty of Science, Botany Department, 2017)
South Africa is the world's third most bio-diverse country, but pressures on this biodiversity are many and widespread. It is now well recognised that protected areas on their own are insufficient to protect biodiversity, and increasing emphasis is placed on developing models for ensuring the persistence of biodiversity in agricultural and rural landscapes. One of the major challenges, especially in rural areas, is the need to reconcile people's need to use natural resources with biodiversity conservation. This study aimed to (1) examine the ecosystem services people derive from the natural vegetation and how this is distributed in space and (2) the effects of land use and topo-edaphic factors on species richness, composition and structure and how this is spatially distributed. I investigated two land-use types, i.e. a rural village and adjacent lightly used game farm(s) by comparing 20 sites under each land-use representing the range of topographic position. I sampled respondent's uses and values, species richness and composition, woody density, structure and composition at these 40 sites. This allowed for comparison between the two land uses but also allowed me to examine the effect of topography and relative soil moisture (both known to have a string influence on vegetation in semi-arid areas), and to relate the ecosystem services to plant species richness, structure and woody composition. People derived a wide range of ecosystem services and this differed with distance from the village and vegetation type. Men and women performed different tasks and had different feelings and derived different use values across the landscapes. Both men and women showed a great appreciation for the thicket forest, Pteronia-dominated and grasslands sites. They recognised these areas and as sacred grounds where they have a strong connection with their ancestors. Women preferred utilising areas closer to the village because they feared crime and wild animals in more remote thicket or forest, while men utilised all areas across the land, but more frequently closer to the village. The older generation had a strong attachment to nature, perceiving it as a provider. The younger generation, especially the young women did not express such a deeply felt connection, but enjoyed getting to see where some of the medicinal plants and useful wood structures were harvested. Younger men would go far into the forest quite regularly, often as far the Great Fish River, when they hunt with their peers. Although a diversity of perceptions were presented, and not all conformed to traditional views and practices, most respondents derived a mix of ecosystem services, with the areas closer to the village providing recreational and direct use value to more people on a more regular basis but spiritual values associated with deep forest persisted, especially among the older generation. Species richness and composition was analysed in relation to Topographic Relative Moisture Index (TRMI), land use and distance from the village to see the effect of topography versus land use on the vegetation. The total number of plant species recorded was 386 for both study sites. Two hundred and ninety two species were recorded in Ntloko and 265 on the game farms. Of the species that were sampled, 121 were recorded in Ntloko only, 94 in the game farms only, and 171 species were shared. The number of useful plant species (fuel, medicine, forage, cultural and edibles) was recorded to be 110, 83 in Ntloko and 63 on the game farms. There was no significant difference in species richness and alpha diversity between the study sites, but the game farms had a higher projected total number of species, reflecting higher beta diversity in the game farms than the communal area. The point-centered quarter method (PCQ) was used to describe woody plant composition, tree density and structure. The woody structure and composition was analysed in relation to the above-mentioned factors and I found no significant difference in the density and overall woody structure and composition between the two study sites. Sites at Ntloko had a positive correlation between soil moisture and woody plant density and a higher density of palatable and unpalatable species. The game farms showed no significant changes in woody plant density with TRMI. This study showed that the communal area maintained comparable plant species richness and vegetation structure and composition to game farms. The rural landscape comprised a gradient from sites close to the village that were heavily impacted, not considered particularly special or sacred but safe, familiar and of utilitarian importance, to sites farther away with denser, less transformed thicket vegetation, which are considered to be of greater cultural, spiritual and aesthetic importance but less safe, familiar and accessible. This suggests that conservation outcomes can be achieved outside protected areas, and that biodiversity is valuable to local residents. Resource management should be implemented to maintain the ecosystem services provided in rural areas in a way that integrates local peoples' perceptions, goals and values with ecological evidence.
Keywords: Uncatalogued